Vai trò của các yếu tố đặc điểm ngân hàng đến tỷ suất sinh lợi cổ phiếu trong giai đoạn COVID-19 - Nguyen Thi Thieu , Quang; Ha Xuan , Thuy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Stock return is a crucial criterion for evaluating investment performance. Nevertheless, previous studies often exclude financial institutions due to their intermediation role and strict regulation of the government. This research investigates the role of bank characteristics in Vietnamese banks’ stock returns considering the COVID-19 pandemic effect. The results reveal negative relationships between liquidity, credit quality, and lending on banks’ stock returns. In particular, bank size and lending play a significant role during the pandemic period. Analyzing the impact mechanisms of these factors additionally shows that bank size, credit quality, and lending impact Vietnamese banks’ stock returns via bankruptcy risk channel. Meanwhile, the liquidity influence is transmitted through idiosyncratic and systematic risks.
Keywords: COVID-19; Bank characteristics; Stock return